2019
DOI: 10.5173/ceju.2019.1876
|View full text |Cite
|
Sign up to set email alerts
|

The industrial revolution for the management of benign prostate obstruction: worldwide publication trends for surgical and medical therapies over the past two decades

Abstract: Introduction Research for management of benign prostate obstruction (BPO) for adult males remains a cornerstone of urology research. This landscape has witnessed the rise and fall of multiple therapies, both surgical and medical. Our aim was to formally evaluate the publication trends for these interventions over the past 20 years. Material and methods A systematic search was performed in a Cochrane style. Data was analysed using the independent t-test and Pearson's cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In accordance with Nettleton et al, we found a growth of scientific research on laser-based therapies for BPH [ 23 ]. Over the last decade, articles on laser procedures in the treatment of BPH were published mainly in urology and nephrology journals experiencing a slight impact factor increase from 2010 to 2015 (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with Nettleton et al, we found a growth of scientific research on laser-based therapies for BPH [ 23 ]. Over the last decade, articles on laser procedures in the treatment of BPH were published mainly in urology and nephrology journals experiencing a slight impact factor increase from 2010 to 2015 (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, bibliometric analyses have been established in Urology to examine the top cited articles [ 18 ], authorship developments [ 19 ], worldwide distribution and exchange of scientific knowledge [ 6 , 20 , 21 ], and citation trends in general [ 8 ]. A rising trend in the field of urological laser procedures has already been described for urolithiasis [ 22 ] and Nettleton et al have shown a notable rise of publications on laser surgery for BPH [ 23 ]. We introduced the first bibliometric analysis thus far focusing on publication origin, authorship, journals and citations regarding laser-based BPH therapy concerning various global aspects.…”
Section: Discussionmentioning
confidence: 99%